PARENTS’ INVOLVEMENT AND ITS EFFECTS ON ENGLISH YOUNG LEARNERS’ SELF- EFFICACY - Christiani Tiwi Sumanti; Retno Muljani (University of Muhammadiyah Malang, 2021)
The research aimed to describe parents’ involvement to support their children’s self-efficacy development in learning English. As a descriptive qualitative study, the research employed observations on two primary school students of grade three, and interviewed their parents and teachers. A set of questions was formulated by the researcher to analyze the influence of parents on their self-efficacy in learning English at home. This study showed that parents' commitment has proven to encourage their children to learn English, and through the Zone of Proximal Development (ZPD) process and learning, particularly their encouragement at home makes the children developed their self-efficacy. Parental participation in English should be taken seriously, particularly in public schools, where there was only a minimum period to learn English at school. It was revealed that parents' involvement in the learning and acquisition of English by the children could contribute positively to their learning achievement and motivation.